PERAN PEKERJA SOSIAL DALAM TRAUMA PASCA BENCANA ALAM MENGGUNAKAN PENDEKATAN KOGNITIF - Rindi Anita; Zahrah Salsabila; Sofiyah Hadi Alhabsyie (Republic of Indonesia Defense University, 2021)
The impact of natural disasters is not only on the material aspect, but also on a person's psychic condition and how that person processes it into memories that will carry over for life. When a person experiences a traumatic event and has a certain response to anything that reminds him of the disaster, this condition occurs because of Acute Stress Disorder and Post Traumatic Stress Disorder. Therefore, this study aims to describe the role of social workers in post-natural disaster trauma using a cognitive approach. This research uses qualitative with library research method. As for the role of post-disaster trauma social workers, apart from being advocates, social workers can also act as counselors who assist disaster victims recovering from their traumatic events. By using a cognitive approach, the recovery process, especially in children, can change negative behaviors and views of the traumatic events they experience and reduce their stigma against similar events.